The role of waqf properties in the development of the Islamic institutions in the Philippines: issues and challenges - Gamon, Alizaman Dumangcag; Tagoranao, Mariam Saidano (IIUM Press, International Islamic University Malaysia, 2018)
The Waqf system continues to be the most successful way by which endowments or revenues accruing from assets can be donated by benefactors,expressly for the welfare of the Muslim Ummah. It is a highly revered act when waqf funds are used in building mosques, madrasahs, orphanages, colleges and universities as well as for providing free medical services for needy Muslims. Waqf can also offer Islamic financial facilities to the deserving. Waqf is considered as an indispensable institution for the socio-economic upliftment of the Bangsomoro people. This research discusses the role of waqf properties in the development of the Islamic institutions in the Phillipines. It also analyses and evaluates the issues and challenges faced by the Muslim minorities in the management and development of waqf properties in a country dominated by Catholic Christians. For sustainable development of waqf properties, this research recommends the establishment of a credible model in management and financing of waqf, which will, in turn, provide a strong support for the establishment of health clinics, Islamic religious centers and educational institutions. This paper concludes that unity among the scholars ('ulama') and Muslim non-governmental organizations through implementation of a uniform waqf management system can strengthen the role of waqf properties in developing Islamic institutions in the Phillipines.